Denture use and a slower rate of cognitive decline among older adults with partial tooth loss in China: A 10‐year prospective cohort study - Xiang Qi; Zheng Zhu; Yaolin Pei; Bei Wu (Aging Medicine)
Abstract Objective Denture use has been shown to improve nutritional intake and diet quality in people with tooth loss. Despite evidence linking tooth loss and dementia, few studies have examined the association between denture use and cognitive decline. We investigated the relationship between denture use and cognitive decline among Chinese older adults with tooth loss. Methods We analyzed data from the Chinese Longitudinal Healthy Longevity Survey 2008–2018, including 27,708 community‐dwelling dentate and edentulous (i.e., who have lost all natural teeth) older adults aged 65 and older. Cognitive function was assessed using the Mini‐Mental State Examination from 2008 to 2018. Linear mixed‐effect models were employed to assess the association of denture use with baseline cognitive function and rate of cognitive decline, adjusting for sociodemographic characteristics, health‐related behavior, and health status. Subgroup analyses evaluated differences in associations among dentate participants with varying degrees of tooth loss (1–9, 10–19, 20–31). Results Compared to non‐denture users, dentate participants who used dentures had better baseline cognitive function (β, 1.032; 95% CI, 0.813–1.251; p < 0.001) and a slower annual decline in cognitive function (β, 0.127; 95% CI, 0.047–0.206; p < 0.01). For edentulous participants, denture use was associated with higher baseline cognitive function (β, 3.063; 95% CI, 2.703–3.423; p < 0.001) but not with the rate of cognitive decline (β, 0.011; 95% CI, –0.082 to 0.105; p = 0.818). Results remained consistent across subgroups of dentate participants with various degrees of missing teeth. Conclusions Denture use may help protect against cognitive decline in older adults with partial tooth loss. This study highlights the potential importance of prosthodontic rehabilitation in preserving cognitive health. Further research is needed to establish a causal relationship between denture use and cognitive function.